UPAYA PENEGAKKAN HUKUM DIREKTORAT RESERSE NARKOBA POLDASU DALAM MENGUNGKAP PEREDARAN NARKOTIKA JARINGAN INTERNASIONAL DI WILAYAH SUMATERA UTARA (STUDI DI POLDA SUMATERA UTARA) - Triyadi, Triyadi; Sahari, Alpi (JURNAL DOKTRIN REVIEW, 2023)
The modus operandi of narcotics trafficking syndicates can easily penetrate the borders of countries in the world through neat management networks and sophisticated technology so that they can enter Indonesia as a transit country or even as a destination country for illegal narcotics trafficking (point of market-state).The formulation of the problem in this research is how the criminal law is regulated against international network narcotics traffickers in the North Sumatra region, and how the Regional Police's Narcotics Research Directorate uncovers the distribution of international network narcotics in the North Sumatra region, as well as what obstacles the Research Directorate finds. Regional Police Narcotics in uncovering international network narcotics distribution in the North Sumatra region. The research method used is empirical juridical legal research. The regulation of criminal law against narcotics dealers is regulated in Chapter Class II, and Class III Narcotics. And the North Sumatra Regional Police's Narcotics Investigation Directorate in uncovering the distribution of international network narcotics in the North Sumatra region took actions or steps such as pre-emptive action, preventive action and repressive action, and the obstacles found included limited police personnel, lack of facilities and infrastructure, and factors that include the ability of organizational resources so that pre-emptive actions, preventive actions and repressive actions are not maximized. Punishment sanctions against international network narcotics traffickers should be accompanied by confiscation of assets which are used for the recovery of the younger generation who have been damaged by narcotics, and additional infrastructure.